Epidemiology of Alternaria leaf spot disease of sunflower - B.S. PATIL, S.G. BORKAR and (Indian Phytopathology, 2002)
In Maharashtra state, 3.5 lakh hectare of land is under sunflower cultivation, Sunflower crop suffers to the infection of many fungal diseases in India, however, the most important is Alternaria leaf spot caused by Alternaria helianthi and other species like A. alternata and A. zinniae causing hundred per cent damage to the crop under severe disease condition. In plain zone of Maharashtra, the damage caused by Alternaria leaf spot on kharif sunflower crop was due to Alternaria helianthi (conidial size 45-145 x 10-30 Î¼m) and was upto 60-75 per cent in severely infected crop. Sunflower fields in Marathwada region of Maharashtra showed a heavy population of Alternaria spore/M 3 in the air, but there was no infection of sunflower crop, suggesting weather parameters as limiting factors in disease development as these play a vital role in the epidemics of plant diseases and therefore, studies on the epidemiological aspect of Alternaria leaf spot pathogen on sunflower was undertaken to formulate a disease forcasting programme.